REAL WORK LECTURE WITH MAINTENANCE PROGRAM FOR ELECTRICAL EQUIPMENT, SECURITY AND AIR CONDITIONER AT THE RUKUN TETANGGA (RT) POST 007/015 IN CIPINANG MUARA VILLAGE, EAST JAKARTA CITY: KULIAH KERJA NYATA (KKN) DENGAN PROGRAM PEMELIHARAAN PERALATAN KELISTRIKAN, KEAMANAN (CCTV) DAN AIR CONDITIONER PADA POS RUKUN TETANGGA (RT) 007/015 PADA KELURAHAN CIPINANG MUARA KOTA JAKARTA TIMUR - Basuki Basuki; Dian Dwi Putra; Indra Widiarto; Suganda P Simanjuntak (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2022)
Real Work Lecture (KKN) is one form of student service to the community and is one part of the Tri Dharma of Higher Education. We, students of Electrical Engineering, Mpu Tantular University, Jakarta, held this Real Work Lecture (KKN) which is expected to help the community in solving problems faced in the Neighborhood Community (Rukun Tetangga) 007 / 015 area, Cipinang Muara sub-district, Jatinegara District, East Jakarta City. In addition, it is hoped that we can gain experience in how to socialize with the community, also as a social person and have good character when engaging in serving the community. The work program plan that we carry out is the maintenance of Electrical Installations, CCTV and Air Conditioners. The result is that we repair the electrical installation by repairing cable connections that are not neat and are considered unsafe. Then we also carry out CCTV maintenance by making repairs so that it is hoped that CCTV can function normally by replacing the damaged power supply. Finally, we carry out maintenance of the Air Conditioner by cleaning the components of the AC so that they function normally with maximum cold air